The Effect of Palliative Care Training on Symptom Management, Rehospitalization and Quality of Life in Chronic Heart Failure: A Randomized Controlled Trial - Gülşah Çamcı; Sıdıka Oğuz (Galenos Publishing House, 2023)
Objective:Palliative care is of great importance because of the poor quality of life and high mortality risk in advanced heart failure. This study was planned as a randomized controlled trial to determine the effect of palliative care training on symptom management, rehospitalization, and quality of life among patients with heart failure.Method:The study included 42 control and 42 intervention groups in patients with class III and IV heart failure according to New York Heart Association classification.Results:According to the Edmonton symptom assessment scale, tiredness (p=0.044), nausea (p=0.016), depression (p=0.002), anxiety (p=0.004), feeling of well-being (p=0.009), leg edema (p=0.021), and total symptom burden (p=0.027) in the first month after discharge and tiredness (p=0.042), nausea (p=0.014) and leg edema (p=0.042) in the third month after the discharge of intervention group was found to be significantly better than the control group. There was no significant difference between groups in quality of life. The rehospitalization rate at the first (p=0.001), third (p=0.001), and sixth (p=0.001) months in the intervention group was found to be significantly lower than the control group.Conclusion:The patients who received palliative care had a better symptom burden in the first month and a lower rehospitalization rate in the first, third, and sixth months. Palliative care should be integrated into the health care system to improve symptom management, increase the quality of life, and reduce rehospitalization among patients with heart failure. Trial Registration: clinicaltrials.gov Identifier: NCT05285163.